Early Planting, Full‐season Cultivars, and Seed Treatments Maximize Soybean Yield Potential. Issue 1 (8th January 2016) - Vossenkemper, Jacob P.; Nafziger, Emerson D.; Wessel, Jeff R.; Maughan, Matt W.; Rupert, Michael E.; Schmidt, John P.
Abstract : Recent findings in the midwestern United States have shown that planting soybean [ Glycine max (L.) Merr.] by early May often increases yield compared to planting in mid‐ to late May. These findings have encouraged earlier planting, but raise questions about how planting date might interact with other management factors. In 58 on‐farm trials in Illinois and Indiana in 2011 and 2012, we found that seed treatment (fungicide + insecticide + rhizobia inoculant) increased plant stand by 4200 plants per acre, with greater effects from early planting than with later planting. Seed treatment also increased yield, by an average of 1.2 bu/acre, but did not interact with planting date or maturity. Planting in late April increased yield only slightly (0.9 bu/acre) compared to planting in mid‐ to late May, and full‐season cultivars yielded 3.8 bu/acre more than short‐season cultivars. Full‐season cultivars yielded 5.5 bu/acre more than short‐season cultivars with early planting, but only 2 bu/acre more planted later. Yield of full‐season cultivars dropped by 2.7 bu/acre from early to normal planting, but those of short‐season cultivars remained unchanged. Although seed treatments may improve stands more with early planting, stands were adequate regardless of planting date or seed treatment, and the decision to use seed treatment can be made independently of cultivar or planting date. These results show that planting full‐season cultivars before short‐season ones, and perhaps choosing slightly fuller season cultivars in general, may improve soybean yields.